The Influence of Physico-Chemical and Bioactivators for Composting of Traditional Market Vegetable Waste - Nyimas Yanqoritha (Jurnal Penelitian Pendidikan IPA, 2023)
Reprocessing organic vegetable waste from conventional markets can have beneficial effects, such as producing bioenergy, reducing the need for inorganic fertilizers, and minimizing the volume of contaminants in the environment. Organic material composting can help lower greenhouse gas emissions and generate income. Physical-chemical factors like temperature, pH, particle size, moisture content, aeration, and CN ratio were used to regulate the breakdown process. Trichoderma harzianum, an effective microorganism, and Trichoderma harzianum helped the degradation process function. High-quality compost is produced by converting organic matter in a bioreactor system, where the solid substrate replenishes nutrients. Based on the optimum point of the decomposition procedure, the analytical findings were achieved. After that the material had been homogenized and aerated, this process took place (oxygen). When the temperature is increased, the active and ripening stages take place, which triggers the breakdown process. The ideal temperature for composting, between 30-45 Â°C, was reached. The temperature steadily drops when the majority of the material has broken down, and the composting process is complete.